Two finite-difference time-domain methods incorporated with memristor - Yang, Zaifeng (2015)
Two finite-difference time-domain (FDTD) methods incorporated with memristor are presented. The update equations are derived based on Maxwell’s equations, and the physical model is given by Hewlett-Packard (HP) lab. The first method is derived by calculating the memristance directly while the second method is derived by the relationship between electric charge and flux. Numerical results are given to discuss the accuracy, efficiency and stability of both proposed methods.